Kreatifitas Dosen pada Pembelajaran Elektronika di Era Digital 5.0 - Harianto, Bambang; Karjadi, Mochamad (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of preparing this work is to find out the forms of lecturer creativity in electronics learning in the digital era 5.0. The literature review method was used to examine relevant literature. Data sources include journal articles, books, policy documents, and interviews with experienced lecturers. Data collection techniques involve literature searches through academic databases and direct interviews with lecturers. Data analysis was carried out descriptively, focusing on identifying lecturers' creative practices in integrating technology in electronics learning. The result of this work is that in the era of electronic learning in Digital 5.0, lecturers have a crucial role in creating innovative learning experiences. By utilizing learning and creativity theories, lecturers can become learning architects who utilize technology effectively and facilitate the development of student creativity. Logistical and geographical challenges in Indonesia require the use of information technology to support distance learning. Lecturers also act as creative facilitators who inspire and guide students towards academic achievement and competitive skills development. The integration of learning theories and creativity in electronic learning allows lecturers to play a central role in directing education towards an innovative and dynamic future. This is in accordance with the objectives of the Higher Education Law no. 12 of 2012, which emphasizes the formation of students who are moral, intellectually capable, creative and have a noble culture.